Nutritional and neurological diagnosis according to period of evolution, neurological level and injury type in rachimedullary patients - Francisca Zamora Pérez; Carmen Margarita Santos-Hernández; Juan E. Bender del Busto; Carlos S. González Martínez; Alejandro P. Terry Zamora (Revista Habanera de Ciencias Médicas)
Introduction: Spinal cord injury (SCI) is a contemporary medical problem characterized by insufficient data on prevalence and weak modelling methodology.